Pengaruh Kemampuan Berempati Terhadap Resolusi Konflik Antarindividu (Studi Kasus: Kelas 07TPLP012 Program Studi Teknik Informatika Universitas Pamulang) - Dyatna, Erika Putri; Hafizh Sahal, Abdullah; Ibnu Adhan, Alvito; Andika Tampati, Rhafly; Abdul Karim, Rizki; Mashuri Hafid, Muhamad (Shofanah Media Berkah, 2025)
Empathy is a social skill that plays a crucial role in maintaining harmonious interpersonal relationships. Understanding others' feelings and perspectives has been shown to influence how individuals respond to conflict. This study employed a qualitative saturation approach aimed at understanding how empathy influences the conflict resolution process in everyday interactions. Data were collected through in-depth interviews with 10 participants from class 07TPLP012. The results indicate that individuals with high levels of empathy tend to be able to de-escalate conflict tensions, foster more honest communication, and reach mutually beneficial resolutions. This study confirms that empathy is a crucial foundation for effective conflict resolution.